Measurement of the inclusive jet cross section in pp collisions at s?=2.76TeV - Collaboration, C. M. S.; Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Erö, J.; Flechl, M.; et al. (My University, 2016)
The double-differential inclusive jet cross section is measured as a function of jet transverse momentum pT and absolute rapidity |y|, using proton-proton collision data collected with the CMS experiment at the LHC, at a center-of-mass energy of ?s = 2.76 TeV and corresponding to an integrated luminosity of 5.43 pb-1. Jets are reconstructed within the pT range of 74 to 592 GeV and the rapidity range |y|<3.0. The reconstructed jet spectrum is corrected for detector resolution. The measurements are compared to the theoretical prediction at next-to-leading-order QCD using different sets of parton distribution functions. This inclusive cross section measurement explores a new kinematic region and is consistent with QCD predictions. © 2016, CERN for the benefit of the CMS collaboration.
Citation: Collaboration, C. M. S., Khachatryan, V., Sirunyan, A. M., Tumasyan, A., Adam, W., Asilar, E., . . . Woods, N. (2016). Measurement of the inclusive jet cross section in pp collisions at ?s = 2.76 TeV. European Physical Journal C, 76(5). doi:10.1140/epjc/s10052-016-4083-z